Association between Serum-Ascites Albumin Gradient and Esophageal Varices in Patients of Cirrhotic Ascites - Alam, SM; Huda, MN; Nurul, MN; I, Towfiq; Haque, MZ; Sarker, A; Sarder, AH (TAJ: Journal of Teachers Association, 2018)
Background: Serum-Ascitic Albumin Gradient (SAAG) can identify ascites related to portal hypertension. Esophageal varix (EV) is another feature of portal hypertension in cirrhosis. This study was done to find out the relation between SAAG and esophageal varices. Materials and methods: It was a cross- sectional descriptive study of 50 cases of cirrhotic ascites. SAAG was measured and upper gastrointestinal endoscopy was done for esophageal varices. Results: Among 50 cases, mean SAAG value 1.77 (±0.45 SD). Esophageal varices were found in 43(86%) cases. All cases with SAAG value >2.0gm/dl had EV. A significant statistical association was found between level of SAAG and the presence of esophageal varices (p=0.01). Conclusion: In patients of cirrhosis, the level of SAAG has positive association with the esophageal varices. This finding may permit us to use SAAG as a preliminary parameter of esophageal varices (EV) especially where endoscopy facilities are not available. TAJ 2014; 27(2): 36-38